2022
DOI: 10.1590/1516-3180.2021.0236.r1.03052021
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis improvement after septorhinoplasty in a sample of allergic rhinitis patients with septal deviation: a quasi-experimental study

Abstract: INTRODUCTIONAllergic rhinitis (AR) is a chronic inflammatory disease that affects almost 30% of the adult population and is associated with other inflammatory diseases. 1 In AR, the upper airway respiratory mucosa becomes inflamed in response to allergen exposure, mediated by the T helper 2 (Th2) immunological response. Common symptoms include sneezing, rhinorrhea, nasal congestion, nasal itching and nasal obstruction. Nasal obstruction is the symptom that is most refractory to medical treatment. 2 The evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Based on the total RCAT scores before and after surgery, both the SMP‐only and SMP + SLIT groups reported significant relief in AR symptoms after surgery. Consistent with previous studies, our study showed that surgical intervention can provide optimal symptom relief in suitably selected candidates 10,11 . Therefore, for AR patients with DNS and/or chronic hypertrophic rhinitis, surgery should be considered.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the total RCAT scores before and after surgery, both the SMP‐only and SMP + SLIT groups reported significant relief in AR symptoms after surgery. Consistent with previous studies, our study showed that surgical intervention can provide optimal symptom relief in suitably selected candidates 10,11 . Therefore, for AR patients with DNS and/or chronic hypertrophic rhinitis, surgery should be considered.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies, our study showed that surgical intervention can provide optimal symptom relief in suitably selected candidates. 10,11 Therefore, for AR patients with DNS and/or chronic hypertrophic rhinitis, surgery should be considered.…”
Section: Surgical Intervention In Patients With Armentioning
confidence: 99%
“…The therapeutic mechanism of AEN is similar to that of PNN and VN. 63 It achieves its goal by blocking the sensation of abnormal stimulation and inhibiting the secretion of inflammatory mediators. 64 Our study found that the efficacy and symptom and sign scores of AEN in the treatment of AR patients without chronic rhinosinusitis and nasal polyps were lower than those of PNN and VN, which may be related to the fact that its innervation of the mucosa is smaller than that of the posterior nasal nerve.…”
Section: Response Rate In Allergic Rhinitis Combined With Chronic Rhi...mentioning
confidence: 99%